Studies On The Mosquito Fauna Of Kerian District With Emphasis On The Mangrove Swamp Ecotype - Ahmad, Abu Hassan (1994)
A survey on the mosqui to fauna of Kerian district and its adjacent area of Bandar Baharu district was taken from August 1986 to December 1990. A total of 157 species of mosquitoes belonging to 17 genera were collected using several methods. Some of the mosquitoes were found to breed only in certain specific ecological zones while others were distributed over a wider area. Aedes amesii, and Uranotaenia latera7is were confined to Cx. sitiens the mangrove swamps. The holes in the trees of the mangrove swamps were the breeding habitat for Ae. amesii. Cx. sitiens breeds in the brackish water pools and water canals that run along the bunds that separate the mangrove swamps from the land. Ur. latera7is larvae were found breeding in the crab holes in the mangrove swamps. Adults rest in these crab holes during the day. The nipah palm axils were used by several species of Aedes and Culex as their breeding habitats.